Outcomes and toxicity of concomitant radioimmunotherapy following PD-1 blockade for locally advanced and metastatic cutaneous squamous cell carcinoma - Kassardjian, Ari A.; Ladbury, Colton J.; Tam, Andrew; Maroongroge, Sean; Xing, Yan; Muddasani, Ramya; Modi, Badri; Amini, Arya (Frontiers in Oncology, 2025)
IntroductionImmune checkpoint inhibitors (ICI) effectively treat advanced cutaneous squamous cell carcinoma (cSCC), yet some patients continue to have disease progression. Combining radiation therapy (RT) with ICI represents a potential therapeutic option, yet limited data exist regarding oncologic outcomes and safety profile.MethodsThis retrospective cohort study examined patients treated with concurrent ICI and RT between April 2019 and November 2022 and stratified by locally advanced or metastatic status. Outcomes included locoregional control (LRC), freedom from distant metastases (FFDM), progression-free survival (PFS), overall survival (OS), and toxicity. Statistical analysis was performed using Kaplan-Meier or Fine-Gray competing risk survival analyses.ResultsThirteen patients (median age 77 years) with locally advanced (53.8%) or metastatic (46.2%) cSCC on cemiplimab (84.6%) or pembrolizumab (15.4%) received concomitant RT using intensity-modulated radiotherapy (69.2%) or stereotactic body radiotherapy (30.8%). With median follow-up of 15.4 months, overall 1-year and 2-year outcomes were OS: 75.2% and 62.7%; PFS: 59.8% and 25.6%; FFDM: 83.8% and 62.4%; LRC 100% and 84.3%, respectively. Locally advanced patients had significantly greater LRC than metastatic patients (100% vs. 56.3%; p<0.001), but no significant difference in PFS, FFDM, or OS. Only one patient experienced grade 3 radiation dermatitis, with no grade 4+ toxicities.ConclusionRadioimmunotherapy demonstrated favorable oncologic outcomes with minimal toxicity. Addition of consolidative RT to ICI therapy may represent a safe and effective approach for this challenging patient population, warranting further prospective investigation.